Determinants of credit utilization among SACCO members in Soroti District, Uganda - Alio, D.; Okiror, J.J.; Agea, J.G.; Matsiko, F.B.; Ekere, W. (African Journal of Rural Development, 2017)
Savings and credit cooperatives have been seen as the most appropriate institution to serve rural households and contribute to poverty alleviation and rural development. However they have been characterized by inadequate credit monitoring and control mechanisms, inefficient loan collection mechanisms and inappropriate loan delivery systems leading to poor loan repayment rates, high loan defaults, and diversion of credit to consumption purposes. This study examinedthe household dynamics that affect productive use of credit among members of Savings and Credit Cooperatives (SACCOs) in Soroti district, Uganda. The findings indicated that women were excluded from institutional credit due to loss of respect and cooperation from their husbands. Consequently women allowed their husbands to control the cash transaction in order to preserve their marriages. Household size was a key significant factor influencing productive use of credit. Therefore, there is need for investment in attitudinal change in men and women in order to reduce gender differences within the household concerning credit use decisions. There is also need to strengthen cooperation among family members in order to utilize the free labour they provide as well as support provided by the different family members especially during repayment of credit.
Keywords: Credit utilization; intra-household dynamics; SACCOs; Soroti; Uganda